2020
DOI: 10.1186/s12909-020-02428-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Distance learning in clinical medical education amid COVID-19 pandemic in Jordan: current situation, challenges, and perspectives

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 1 publication
6
38
2
3
Order By: Relevance
“…Investigations had been carried out in the form of numerous studies to determine students' perceptions and attitudes towards the completely digital education during the coronavirus outbreak, and one of the popular topics discussed was the challenges faced. For example, [11] found that the biggest concern among students in Jordanian medical schools was poor Internet coverage, followed by Internet data limitation, learning platform variation and insufficient devices. Similarly, the findings of another study showed that 69% of 762 students from two universities in Romania faced technical problems with the platform used by the university, whereas 14.8% had inadequate devices and mobile connection.…”
Section: A Students' Perceptions Of Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations had been carried out in the form of numerous studies to determine students' perceptions and attitudes towards the completely digital education during the coronavirus outbreak, and one of the popular topics discussed was the challenges faced. For example, [11] found that the biggest concern among students in Jordanian medical schools was poor Internet coverage, followed by Internet data limitation, learning platform variation and insufficient devices. Similarly, the findings of another study showed that 69% of 762 students from two universities in Romania faced technical problems with the platform used by the university, whereas 14.8% had inadequate devices and mobile connection.…”
Section: A Students' Perceptions Of Online Learningmentioning
confidence: 99%
“…On the positive side, students do acknowledge the advantages of e-learning, such as being able to continue their education remotely from the comfort of their homes, the usefulness of having recorded videos to facilitate their studying and revision process and the development of their self-directed learning skills [14]. Results from other literature showed comfortable learning environment as one of the most prevalent benefits of online education in addition to the flexibility of learning anytime and anywhere and the reduction of transportation time and expenses [5], [11]. For enhancing online learning, students suggested that the interaction be improved and the workload be reduced [14].…”
Section: A Students' Perceptions Of Online Learningmentioning
confidence: 99%
“…In contrast, as a consequence of the mandatory social isolation, in-person classes in Lima, Peru have been cancelled to start the distance learning modality at the national level. [ 10 11 ] This teaching mode requires the use of uncommon learning methods and the acquisition of new habits by students, which could significantly affect not only their academic performance but also their mental health. [ 12 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the strict need to keep social distances due to the recent COVID-19 worldwide outbreak has resulted in the temporary closure of universities in many countries and denied medical students from accessing clinical wards [ 4 , 5 ]. From an educational standpoint, this promotes the need for clinical training methods that do not require bedside didactic activities and that do not necessarily entail continuous direct supervision by experienced doctors [ 6 , 7 ]. Examples of these methods are simulators, which were developed not only to support learning of specific medical procedures, such as laparoscopy [ 8 ], but also to train students in clinical diagnostic reasoning as with virtual patient simulators (VPSs) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%